Monitoring success: on a fundamental principle of financial regulation - Marjit, Sugata (2003)
Financial disasters have become common round the world. Their nature has been complex and varied, but the strong common link is that they have all underscored the importance of regulatory supervision of financial deals. This essay traces an even more fundamental relationship among apparently dispersed and unrelated problems. This has to do with the lack of monitoring of any system which performs well. - Reproduced.
Keywords: Financial policy